Integration of Economics Identity and the Concept of Hayatan Tayyibah to Address Hustle Culture: A Qur’anic Perspective - Al Fahrizal; Khofawati Khoiriyyah (Universitas Islam Cordoba Banyuwangi, 2026)
Behind global economic growth lies a workforce that serves as its primary engine, yet is frequently trapped in hustle culture—a work culture that glorifies performative productivity at the expense of psychological well-being. This article identifies fundamental issues in modern work culture that establish incessant busyness as a standard for self-validation; meanwhile, the discourse on Islamic Work Ethic (IWE) tends to remain stagnant at a normative-spiritual level, emphasizing intention and reward without addressing the structural identity crisis of economic actors. Consequently, the economic identity of the Ummah becomes alienated from Qur'anic values and absorbed into the currents of secular materialism. This study aims to reconstruct the Qur’anic work ethic not merely as a theological obligation, but as a solution to the economic identity crisis. This research employs a qualitative method with a library research approach. Data collection was conducted through an inventory of Qur'anic verses related to well-being (specifically Q.S. An-Nahl: 97 and other relevant verses), alongside sociological literature on toxic productivity. Data analysis techniques utilize the Maudhu’i (thematic) Tafsir model by Al-Farmawi, paired with Content Analysis of authoritative commentaries (Tafsir Ibn Kathir and Tafsir Al-Maraghi). Specifically, this research dissects the concept of Hayatan Tayyibah using the analytical lens of Identity Economics by George Akerlof and Rachel Kranton to reformulate the utility function of Muslim workers. The findings indicate that Hayatan Tayyibah offers a reconstruction of economic identity based on Qana'ah (inner contentment) and Barakah (blessings), serving as stabilizing variables in the worker's utility function. In contrast to the exploitative nature of hustle culture, this concept integrates material and spiritual orientations, transforming the perception of work from a pursuit of external validation into a mentally healthy expression of servitude (ubudiyah). This article contributes a new theoretical framework for the development of Islamic Industrial Psychology and offers alternative human resource management policies that prioritize the psycho-spiritual sustainability of workers amidst the pressures of global capitalism.